Antimicrobial susceptibility profiles and species distribution of medically relevant Nocardia species: Results from a large tertiary laboratory in Australia. (March 2020) - Tan, Yen Ee; Chen, Sharon C.-A.; Halliday, Catriona L.
Highlights: Overall, 9.3% of the tested Nocardia spp. isolates displayed sulfonamide resistance. N. farcinica accounted for the highest number of sulfonamide-resistant strains. 59.3% of Nocardia were imipenem-resistant; high imipenem resistance in N. cyriacigeorgica is atypical to its drug pattern. A high level of intermediate resistance to tetracyclines was observed in most species. Linezolid and amikacin remain good empirical options for nocardiosis treatment. Abstract: Objectives: There are limited surveillance studies on the epidemiology and resistance rates of Nocardia spp. in Australia, particularly in the jurisdiction of New South Wales. This study aimed to investigate the species distribution and antimicrobial susceptibility of a large number of contemporary (2011–2016) clinical Nocardia spp. referred to a large tertiary hospital in Sydney, Australia. Methods: A total of 270 Nocardia spp. isolates identified to species level by dual-target gene sequencing were investigated. Antimicrobial susceptibility testing was performed using a Sensititre™ RAPMYCOI panel, with the minimum inhibitory concentration (MIC) range and geometric mean MIC obtained for each species and drug combination. Antimicrobial susceptibility profiles and species distribution were analysed. Results: The respiratory system is the most affected site in nocardiosis. In this study, Nocardia nova complex was the most frequently isolated Nocardia spp. ( n = 80; 29.6%), followed by Nocardia cyriacigeorgica ( n = 61; 22.6%), Nocardia brasiliensis ( n = 52; 19.3%) and Nocardia farcinica ( n = 38; 14.1%). Of the tested isolates, 9.3% and 59.3% displayed resistance to trimethoprim/sulfamethoxazole (SXT) and imipenem, respectively. Nocardia farcinica accounted for the highest number of SXT-resistant isolates. High imipenem resistance in N. cyriacigeorgica is atypical to its drug pattern but has been reported elsewhere. All tested isolates remained susceptible to linezolid, with only 0.7% exhibiting resistance to amikacin. Conclusion: Linezolid and amikacin remain good empirical options for treatment of nocardiosis. Routine antimicrobial susceptibility testing of Nocardia is advisable with the detection of sulfonamide resistance and atypical antibiograms in this study.